The use of dendritic fibrous nano-titanium to enhance the initial characteristics and durability of lightweight concrete - Hossein Javan; Amin Honarbakhsh; Seyed Mojtaba Movahedifar; Mehdi Nobahari; Rahele Zhiani (Scientific Reports)
Abstract The utilization of nanoparticles in concrete has been propelled by their advantageous attributes, such as their fine particle size and remarkable reactivity. To enhance these properties, various nanoparticles can be integrated into the lightweight concrete matrix. We introduce a novel technique to produce TiO2 structures resembling dandelions, featuring interfaces between anatase and TiO2 phases as well as a distinct outer layer. This approach utilizes a deep eutectic solvent-tuning method that is both user- and environmentally friendly. The formation of this remarkable external covering is attributed to the hierarchical arrangement of two-dimensional ultrathin nanosheets with mesopores in a three-dimensional configuration. The primary focus of this study is the utilization of DFNT, a nanoparticle possessing a three-dimensional structure, within the matrix of lightweight concrete. To conduct this study, concrete cases with congestion of 1000 kg/m3 were fabricated and subjected to testing. We sought to evaluate the effect of different weight ratio proportions of DFNT on the enduring characteristics of lightweight concrete, such as the contraction caused by drying, the degree of openness, the capacity to absorb water, and the speed at which ultrasonic waves travel. The inclusion of DFNT induces a transformation in the microstructural composition of lightweight concrete, shifting it from a loose needle-like structure to a more compact and cohesive microstructure characteristic of cementitious composites. Furthermore, DFNT enhances the lightweight concrete matrix by occupying the empty spaces, tiny fractures, and gaps present within it.